Diathesis Hemorrhagic, Coagulation and Fibrinolytic System - Rizky Amalia Putri; Muhammad Noor Diansyah; Ami Ashariati Ashariati; Siprianus Ugroseno Yudho Bintoro; Putu Niken Ayu Amrita; Merlyna Savitri Savitri; Pradana Zaky Romadhon (Biomolecular and Health Science Journal, 2022)
Bleeding is one of the most common complaints when coming to the hospital which can be mild to life-threatening. The balance of the impaired hemostasis system allows for abnormal bleeding such as hemorrhagic diathesis. Balance between blood clotting and bleeding is always maintained in the body under normal physiology. The coagulation system stops existing bleeding with vasoconstricts of blood vessels and the formation of early platelet plugs, this blockage is strengthened by the presence of a cascade of coagulations to form stable and sturdy blockages. Once bleeding has stopped, the fibrinolytic pathway is initiated to dissolve the blood clot to restore normal blood flow. balance the coagulants, fibrinolytic and inhibitor systems, creating a perfect physiological balance. Hemostatic imbalance is a global problem that can lead to thrombosis or hemorrhage.